2015
DOI: 10.1186/s12960-015-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Using a human resource management approach to support community health workers: experiences from five African countries

Abstract: BackgroundLike any other health worker, community health workers (CHWs) need to be supported to ensure that they are able to contribute effectively to health programmes. Management challenges, similar to those of managing any other health worker, relate to improving attraction, retention and performance.MethodsExploratory case studies of CHW programmes in the Democratic Republic of Congo, Ghana, Senegal, Uganda and Zimbabwe were conducted to provide an understanding of the practices for supporting and managing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 21 publications
(16 reference statements)
1
63
0
1
Order By: Relevance
“…Some of these have been identified as being significant factors in motivation of CHVs (13, 14, 17, 18, 25, 26). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these have been identified as being significant factors in motivation of CHVs (13, 14, 17, 18, 25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…Individual, group, and program factors have each been shown to influence the performance of CHVs (1, 3, 5, 6, 815, 1719, 25). Factors previously reported to result into improved performance include the female gender, regular supervision and provision of feedback, higher education, the availability of job aides and other tools, and feeling “connected” with the system (3, 5, 6, 911, 13, 14, 17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…These Millennium Development Goals comprised the backbone of what was described as 'an unprecedented agreementamong developed countries, developing countries, and international agenciesto work towards a world in which sustaining development and eliminating poverty would have highest priority ' (World Bank 2003, 7). In this context, training interventions were aimed at enhancing a CHW's performance as an instrument of these widely-endorsed health policies, rather than promoting learning outcomes per se (see Hongoro and McPake 2004;Raven et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on CHWs in other contexts has also supported innovations in CHW supervision going beyond their facility-based supervisors [27][28][29]. MANIFEST also found that non-monetary incentives such as T-shirts, certificates and musawo (doctor) status in the community motivated VHTs to continue working.…”
Section: Strengthening Chwsmentioning
confidence: 96%